Perceptions of Faculty Members at Jordanian Universities for the Efficiency of Crisis Management at the University (Corona Pandemic as a Model) - Murtada, Mariam Ayed; Al-Momani, Mohammad Omar; Khalidi, Reem S.; Alsedawi, Amal Abdelfattah (Journal of Ecohumanism, 2024)
This study aims to find out the perceptions and opinions for faculty members from Jordanian universities about the efficiency of crisis management at the university, through (planning in crisis management, information in crisis management, communications in crisis management, decision-making in crisis management, and the crisis management team). Corona crisis as a model for crises. The study followed the descriptive and analytical approach, whereby the study population consisted of all faculty members at Jordanian universities, and the questionnaire was used as a tool for data collection. Then it was distributed to the sample of the study randomly that its (163) members. Then the data analyzed through the statistical program SPSS. The results showed that the perceptions of faculty members from Jordanian universities are that the level of efficiency crisis management in the university is moderate, especially during the Corona pandemic crisis. So that crisis management at the university needs to be restructured. The study recommended variable future studies in the same for a different population in the sample